Unity in the Book of Isaiah - Rossi, Benedetta; Irudayaraj, Dominic S.; Hens-Piazza, Gina (Library of Hebrew bible/Old Testament studies, 2024)
"Approaches the Book of Isaiah through the concept of unity in order to explore the challenges of this perspective and also outline new directions in the unity movement and encourage further holistic readings of the text"--